Working at workouts : commercial real estate debt in distress - Furfine, Craig ([London] : SAGE, 2016)
In 2010 Drive Property Solutions, a special servicing firm in Chicago had partnered with Spiner Capital to win an FDIC auction of distressed debt. Included in that auction was the defaulted mortgage note on Northwinds Community Crossing, a retail strip mall in suburban Savannah, Georgia, which had been in default since November 2009. Sam Schey, an asset manager at Drive, needed to decide how to maximize recoveries from the nonperforming loan.
Originally Published in: Furfine, C. (2011). Working at Workouts: Commercial Real Estate Debt in Distress (case revised 16/10/2012; teaching notes revised 24/11/2014). 5-411-754. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Real estate management -- Case studies